Athletes’ self-compassion and emotional resilience to failure: the mediating role of vagal reactivity - Zhang, Nan; Huang, Jiasheng; Yao, Jiaxin (Frontiers in Psychology, 2023)
Whether athletes’ self-compassion predicts their emotional resilience to failure has yet to be empirically tested. Moreover, as an important physiological process of stress regulation, vagal reactivity is a plausible physiological mechanism for this relationship. Through a laboratory-based observational study of 90 college athletes, this research explores the influence of athletes’ trait self-compassion on their emotional resilience when recalling failure, and examines whether vagal reactivity plays a mediating role. The results show that self-compassion did not significantly predict athletes’ positive emotions but did significantly predict better recovery from negative emotions after recalling failure events. Furthermore, vagal reactivity was a significant mediator between self-compassion and recovery from negative emotions.